Comportamientos contraproducentes en el trabajo: diseño y validación de una escala (2012)
Counterproductive organizational behaviors (COB) are voluntary and discretionary actions that violate significant organizational norms. This article describes the steps followed for the development and validation of a scale to measure them. From the literature review, focus group, and expert opinion, a preliminary scale with 37 items was designed, which was applied to 336 Argentine employees. An exploratory factor analysis showed a three-factor structure, which was confirmed by a confirmatory factor analysis. The internal consistency of the factors was greater than .80. The discriminant validity was examined through correlations with measures of justice perceptions, affectivity, satisfaction, job stress, and social desirability. We discuss the importance to have measurement instruments that reflect the organizational culture of Latin American companies.